Social mobility management tools for civil servants - Vladimir Alexandrovich Kondrashkin (Вестник Майкопского государственного технологического университета, 2023)
The article considers social mobility as an object of management in the field of state civil service, and substantiates its relevance and highlights problems that need to be studied in more detail; one of them is the search for effective tools for managing social mobility of public civil servants. Social mobility as a social phenomenon of modern society is understood as a key personal and institutional characteristic of a designated area that has a number of features, one of which is its strict regulation by legislative and regulatory acts. The organized nature of the social mobility of civil servants, along with positive effects, can give the opposite result. The article also provides data of sociological studies confirming the existence of systemic problems in the field of public civil service and the need to optimize activities of the employees themselves, whose social mobility is considered as one of the mandatory professional competencies. The tools for managing social mobility in government agencies presented in the article are the result of domestic and foreign experience analysis, as well as personal experiences of the author.